State of the art reviews: Resistance training for children and adolescents - Faigenbaum, A. (American Journal of Lifestyle Medicine, 2007)
Although much of what we understand about the stimulus of resistance exercise has been gained by exploring the responses of adults to various training protocols, research into the effects of resistance exercise on children and adolescents has increased over the past decade. Despite outdated concerns that resistance training was ineffective or unsafe for youth, research increasingly suggests that resistance training can be a safe and effective method of exercise for children and adolescents provided that appropriate training guidelines are followed. In addition to enhancing motor skills and sports performance, regular participation in a youth resistance training program has the potential to positively influence several measurable indices of health. It helps strengthen bone, facilitate weight control, enhance psychosocial well-being, and improve one's cardiovascular risk profile. Furthermore, a stronger musculoskeletal system will enable boys and girls to perform life's daily activities with more energy and vigor and may increase a young athlete's resistance to sports-related injuries. Along with other types of physical activity, a properly designed youth resistance training program can offer observable health value to children and adolescents when appropriately prescribed and supervised. Volltext siehe: http://www.eleikosport.se/gymfitness/admin/files/20090810115014.pdf